What Matters the Most: On-Site vs Remote Service Delivery - Bronet, Dr. Jose (Global journal of Business and Integral Security, 2024)
Professional Services in SaaS or Software companies around the Globe have experienced a shift, accelerated by COVID-19, towards delivering work Remotely. Some companies still work under the assumption that the rules of Quality of Service have not changed. This study challenged this assumption and made key counterintuitive discoveries that can lead Professional Services organisations to maximise their contribution to the company’s Revenue. Some of these counterintuitive discoveries include revealing that how the personnel are physically perceived by customers plays a bigger role when working Remotely. It also reveals that when working On-site, customers assess the different factors of service quality more independently, and when working remotely, these factors have much stronger entanglements. This research provides actionable insights and recommendations, helping Professional Services organisations make the right decisions depending on their delivery model so that they can have a bigger impact on the Revenue of the companies they are part of.